2014
DOI: 10.1371/journal.pone.0089400
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Smoking and Ectopic Pregnancy: Why Nicotine Is BAD for Your Fallopian Tube

Abstract: Epidemiological studies have shown that cigarette smoking is a major risk factor for tubal ectopic pregnancy but the reason for this remains unclear. Here, we set out to determine the effect of smoking on Fallopian tube gene expression. An oviductal epithelial cell line (OE-E6/E7) and explants of human Fallopian tubes from non-pregnant women (n = 6) were exposed to physiologically relevant concentrations of cotinine, the principle metabolite of nicotine, and changes in gene expression analyzed using the Illumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
1
25
0
2
Order By: Relevance
“…These data suggest that the increased number of ciliated cysts reflects impaired ciliogenesis in the Fallopian tube epithelium of women who smoked. Cigarette smoking is a major risk factor for tubal ectopic implantation (Shaw et al, ), and we previously showed that luminal epithelial cells of the Fallopian tube of women who smoke have altered rates of cell turnover and a higher potential to lose cilia (Horne et al, ). Results from this study provide additional evidence that smoking changes the structure of the Fallopian tube epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…These data suggest that the increased number of ciliated cysts reflects impaired ciliogenesis in the Fallopian tube epithelium of women who smoked. Cigarette smoking is a major risk factor for tubal ectopic implantation (Shaw et al, ), and we previously showed that luminal epithelial cells of the Fallopian tube of women who smoke have altered rates of cell turnover and a higher potential to lose cilia (Horne et al, ). Results from this study provide additional evidence that smoking changes the structure of the Fallopian tube epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, mothers exhibiting persistent smoking patterns during the second and third trimesters had higher depressive symptomatology and stress relative to non-persistent smokers [36]. Recent research continues to demonstrate that tobacco and nicotine exposure are associated with adverse pregnancy outcomes, including damage to the umbilical cord structure [37], miscarriage [38], increased risk for ectopic pregnancy [39] and preterm delivery [23,40]. Smoking in pregnancy is also associated with increased infant morbidity and mortality [8,41-45], and second-hand smoke is associated deleterious health effects on newborns, which include increased risk for respiratory and ear infections, sudden infant death syndrome, behavioral dysfunction and cognitive impairment [46].…”
Section: Tobaccomentioning
confidence: 99%
“…BAD-and BCL2-specific immunolabeling was localized to Fallopian tube epithelium. So, smoking may alter tubal epithelial cell turnover and is associated with structural, as well as functional, changes that may contribute to the development of EP [50]. Moreover, cigarette smoking increases transcription of prokineticin receptor 1 (PROKR1), a G-protein-coupled receptor [49].…”
Section: Risk Factors Affecting the Incidence Of Ectopic Pregnancymentioning
confidence: 99%